Engaging Students in Environmental Research Projects: Perceptions of Fluency With Innovative Technologies and Levels of Scientific Inquiry Abilities - Ebenezer, Jazlin; Kaya, Osman Nafiz; Ebenezer, Devairakkam Luke (Wiley-Blackwell, 2011)
The purpose of this mixed-method study was to investigate the changes in high school students' perceptions of fluency with innovative technologies (IT) and the levels of students' scientific inquiry abilities as a result of engaging students in long-term scientific research projects focusing on community-based environmental issues. Over a span of 3 years, a total of 125 ninth- through twelfth-grade students participated in this study. A project-specific Likert-scale survey consisting of three parts (fluency with All Technologies, GPS/GIS, and CBL2/EasyData) was administered to all students as a pre- and post-test. At the end of the study, 45 students were randomly interviewed and asked to elaborate on the changes in their perceptions of fluency with IT. The results indicated statistically significant increases (p < 0.001) in students' perceptions of their fluency with IT. Qualitative analysis of students' interview results corroborated the statistical findings of students' changes in perceptions of their fluency with IT. Students' research papers based on the environmental studies conducted at the interface of classroom and community were analyzed using the Scientific Inquiry Rubrics, which consist of 11 criteria developed by the researchers. Results indicated the students' abilities to conduct scientific inquiry for 7 out of 11 criteria were at the proficient level. This study clearly points to the correlation between the development of IT fluency and ability levels to engage in scientific inquiry based on respective competencies. Ultimately, this research study recommends that students' IT fluency ought to be developed and assessed concurrently with an emphasis on contemporary higher order scientific inquiry abilities. (C) 2010 Wiley Periodicals, Inc. J Res Sci Teach 48: 94-116, 2011
Keywords: biology/life science; science teacher education; technology education; secondary